2017
DOI: 10.3847/1538-4357/835/1/98
|View full text |Cite
|
Sign up to set email alerts
|

ALMA Deep Field in SSA22: Source Catalog and Number Counts

Abstract: We present results from a deep 2′×3′ (comoving scale of 3.7 Mpc×5.5 Mpc at z = 3) survey at 1.1mm, taken with the Atacama Large Millimeter/submillimeter Array (ALMA) in the SSA22 field. We observe the core region of a z = 3.09 protocluster, achieving a typical rms sensitivity of 60 μJy beam −1 at a spatial resolution of 0 7. We detect 18 robust ALMA sources at a signal-to-noise ratio (S/N)>5. Comparison between the ALMA map and a 1.1mm map, taken with the AzTEC camera on the Atacama Submillimeter Teles… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
112
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 80 publications
(128 citation statements)
references
References 104 publications
16
112
0
Order By: Relevance
“…[C II] emission has also been detected in ALMA-LAB1b with a secured redshift of 3.0993 ± 0.0004 (Umehata et al 2017b). …”
Section: Lab1mentioning
confidence: 81%
See 2 more Smart Citations
“…[C II] emission has also been detected in ALMA-LAB1b with a secured redshift of 3.0993 ± 0.0004 (Umehata et al 2017b). …”
Section: Lab1mentioning
confidence: 81%
“…21 The National Radio Astronomy Observatory is a facility of the National Science Foundation operated under cooperative agreement by Associated Universities, Inc. Matsuda et al 2017, in preparation). Another two LABs, LAB12 and LAB14, had been covered by a deep field in SSA22 (Umehata et al 2015(Umehata et al , 2017b in band 6 with a central frequency of 263 GHz. The data were reduced with the CASA package in a standard manner (for details, see Umehata et al 2017b andY.…”
Section: Jcmt/scuba-2 Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…3, we compare the depth and areal coverage of the ALMA archival data in COSMOS at ALMA Band 6 and 7 to the selected existing contiguous ALMA continuum deep fields: Aravena et al (2016; see also Walter et al 2016); Dunlop et al (2017); and Franco et al (2018;PI: D. Elbaz). Other ALMA deep fields (e.g., Hatsukade et al 2016;Umehata et al 2017) have similar properties and are therefore not shown. We compute the depth of each ALMA image by converting its rms noise to an equivalent flux at observed-frame 1.1 mm assuming a modified blackbody with β = 1.8.…”
Section: Data and Photometrymentioning
confidence: 99%
“…This suggests that the CO(3-2) (or dust) detection of the galaxies depends on (but not necessarily) the large-scale structure. Umehata et al (2015Umehata et al ( , 2017 argued that there is a concentration of the 1.1 mm continuum sources in the node of protocluster SSA22, where filamentary structures meet. If it also applies to our case, the detection in the region of highest surface densitymay be mirroring the preferential place of gas detection withincertain large structures of the protocluster, e.g., projected filaments or the node, where the gas is infalling or being accreted.…”
Section: Gas Content In a Protoclustermentioning
confidence: 99%